Diagnostic Performance of Neurofilaments in Chinese Patients With Amyotrophic Lateral Sclerosis: A Prospective Study - Li, Da-Wei; Ren, Haitao; Jeromin, Andreas; Liu, Mingsheng; Shen, Dongshao; Tai, Hongfei; Ding, Qingyun; Li, Xiaoguang; Cui, Liying (Frontiers in Neurology, 2018)
Objectives: To reduce the diagnostic delay and as biomarkers in support of drug development in amyotrophic lateral sclerosis(ALS), we aimed to evaluate the diagnostic accuracy of CSF neurofilament (Nf), tau protein and inflammatory factors (IL-10, IL-6, GMCSF, IL-2 and IL-15) in Chinese ALS patients. Methods: In a prospective study, we measured CSF of 85 patients for phosphorylated Nf heavy chain (pNfH), Nf light chain (NfL), Tau, pTau and inflammatory factors concentrations. Detailed clinical data, laboratory tests, neuroimaging and neurophysiological findings were recorded. Results：The concentration of pNfH and NfL were higher in ALS group compared with control group. At a cut-off level of 1104 pg/mL for pNfH, a 100% diagnostic sensitivity, a 68.8% specificity, a 0.907 AUCs were achieved. At a cut-off level of 1139 pg/mL for NfL, a 96.2% diagnostic sensitivity, a 56.3% specificity, a 0.775 AUCs were achieved. Tau, pTau, IL-2, IL-6, IL-10, IL-15 and GMCSF concentrations in the ALS group and the control group were not statistically significant (p>0.05). The concentration of pNfH in CSF was correlated with the disease duration (r=-0.475, p<0.001) in the ALS group. Conclusion: This is first prospective study in a Chinese ALS cohort and confirm the diagnostic utility of neurofilaments.